Ocena stanu i rozwoju branż polskiego przemysłu spożywczego - Gornowicz, Mirosław (Evaluation of the Development of Food Industry Branches in Poland, 2006)
The study concerns 18 food industry branches. The source materials comprise statistical publications referred to in the text. The position of particular food industry branches is determined applying the following criteria: number of enterprises, employment level, fixed assets, ownership capital and revenues. It is found that the meat, dairy, brewing and fruit-and-vegetable processing industry occupy the dominant position. It is also demonstrated that the industrial branches related to processing animal raw materials are characterized by lower labour efficiency, as compared with other branches, which is caused primarily by a lower value of their fixed assets. However, this situation is gradually changing for the better due to major investments. The financial status of the above industrial branches is estimated based on: net profit, financial liquidity and indebtedness. The general situation of the Polish food industry was satisfactory in the first year of our membership in the European Union, but the position of particular industrial branches differed considerably.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 263-267